Pengaruh Tugas Individu dan Kelompok Terhadap Hasil Belajar dalamTeks Deskripsi Kelas VII di SMP - Rahmaningrum, Friska; Septiana, Ika; Mukhlis, Mukhlis (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to describe the effect of individual and group assignments on learning outcomes in class VII descriptive texts at junior high school. This research was conducted in class VII F and VIIG each class amounting to 32 students. To obtain the necessary data, the researchers used methods in the form of observation, written tests, non-written tests, documentation, while the analytical method used was quantitative data methods in the form of numbers. Data analysis techniques used by researchers are validity test, reliability test, multicollinearity test, heteroscedastic test, normality test, hypothesis testing. The results of this study are the influence of learning outcomes in descriptive texts on individual and group assignments. From the results of the hypothesis that students who are given individual assignments have better learning outcomes of 0.579 compared to the learning outcomes of 0.564 produced by students who are given group assignments Keywords: Description Text, Quantitative Method, Assignments, Learning Outcomes